Proceedings of the Third Nordic Conference on Human-Computer Interaction 2004
DOI: 10.1145/1028014.1028068
|View full text |Cite
|
Sign up to set email alerts
|

Emotional response patterns and sense of presence during video games

Abstract: We investigated the emotional response patterns and sense of presence elicited by video games with different characteristics (i.e., Tetris, Super Monkey Ball 2, Monkey Bowling 2, and James Bond 007: NightFire) among 37 undergraduates. We also examined the moderating influence of the sensation seeking and self-forgetfulness traits on the responses. Participants self-reported their emotional responses, defined in terms of joy, pleasant relaxation, anger, fear, and depressed feeling, and sense of presence. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 25 publications
1
51
0
3
Order By: Relevance
“…Since the rise of the internet in the mid 1990s, however, mental health research has turned increasingly toward the computer-as-conduit model, in which processing power is harnessed precisely to transmit facilitator and user communications. Recent studies have concentrated on technical and cognitive requirements for creating the illusion of virtual therapist presence (Riva et al, 2002) or immersive user presence in a virtual world (Ravaja et al, 2004). Improved graphics and processing speed enable real-time animation of on-screen interlocutors, allowing users to interact with the inhabitants of projected narrative worlds both verbally and physically (e.g.…”
Section: Online Revolution: Changing Horizons For Therapeutic Video Gmentioning
confidence: 99%
“…Since the rise of the internet in the mid 1990s, however, mental health research has turned increasingly toward the computer-as-conduit model, in which processing power is harnessed precisely to transmit facilitator and user communications. Recent studies have concentrated on technical and cognitive requirements for creating the illusion of virtual therapist presence (Riva et al, 2002) or immersive user presence in a virtual world (Ravaja et al, 2004). Improved graphics and processing speed enable real-time animation of on-screen interlocutors, allowing users to interact with the inhabitants of projected narrative worlds both verbally and physically (e.g.…”
Section: Online Revolution: Changing Horizons For Therapeutic Video Gmentioning
confidence: 99%
“…Reports of cyber sickness symptoms have been significantly correlated with immersive tendencies independently of the game played (Ling, et al, 2013). Research has also found that emotional responses and game engagement varies according to personality traits (e.g., sensation seeking) (Ravaja et al, 2004). …”
mentioning
confidence: 99%
“…However, negative experiences such as frustration or tension (Gilleade and Dix, 2004) indisputably contribute to the challenge of a game and are presumably essential in order for the overall game experience to work. Consequently, a lot of successful games are designed to gradually evolve from negative emotions in the face of challenge to positive emotional experiences, such as fl ow, when the skills are in balance, and the challenge is overcome (Keeker et al, 2004;Ravaja et al, 2004). In a similar vein, Bryant and Davis (2006) have argued that gamers strive to maximize their pleasure, which often inevitably includes that they sacrifi ce immediate gratifi cation for the greater enjoyment that awaits them as soon as they master the next level.…”
mentioning
confidence: 99%